An underwater sensing system for monitoring radioactivity in the marine environment - TSABARIS, C.; THANOS, I. (Mediterranean Marine Science, 2004)
We describe a set up and an application for an autonomously working, radioactivity sensing instrument, usable in seawater and river environments. The system is based on a N aI scintillator with the appropriate specifications for use in the marine environment and for real time acquisition. It is simple, stable for long - term monitoring, and of low consumption. Many tests were carried out for the linearity and the stability of the electronics. The investigation of energy resolution and energy calibration of the sensor was performed in the laboratory using various reference point radioactive sources. The system was also deployed in a water tank in order to measure background radiation in the water and low volumetric activity of 137Cs (17 Bq/m3). Appropriate software identifies qualitatively the low level137Cs contribution to the measured γ-ray spectrum.